1970
DOI: 10.1017/s0021859600017597
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal production of Andropogon gayanus. I. Seasonal changes in yield components and chemical composition

Abstract: SUMMARYChanges in yield and quality of an Andropogon gayanus sward were traced throughout the 1964 wet season and part of the following dry season.Quality, in terms of crude-protein content, was highest at the beginning of the wet season, but yield increased to a maximum at the beginning of the dry season. Once flowering was completed in October, herbage quality fell to a very low level. It was concluded that the best time to cut for hay was in early October, at which time the crude-protein content showed a sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
3

Year Published

1975
1975
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 9 publications
(10 reference statements)
1
11
0
3
Order By: Relevance
“…Several studies have been conducted to test the effect of age of cutting on both yield and quality factors. Haggar (1970), Saleem (1972) and Omaliko (1980) commented that cutting frequency was the major factor that influenced the DM production and nitrogen concentration of P. maximum.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted to test the effect of age of cutting on both yield and quality factors. Haggar (1970), Saleem (1972) and Omaliko (1980) commented that cutting frequency was the major factor that influenced the DM production and nitrogen concentration of P. maximum.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown the interval of harvesting to affect both herbage yield and quality (Oyenuga. 1959;I960;Haggar, 1970;Saleem, 1972). Generally, they showed that the more infrequent the cutting, the higher the DM yield, the proportion of stem and the crude fibre concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation of mineral elements dynamics showed that low content at early fruiting/seeding season reflected the excessive draw on minerals, followed by probable stabilization of the plant minerals pool at mid season fruiting and the marginal increases in mineral contents of seeds at late season. Previous studies on mineral elements of food crops attributed the values to variety and soil conditions Reports on the dynamics of mineral elements uptake by growing plants demonstrate complementary absorption patterns [3,6,9]. Magnesium, copper and iron are drawn for enzyme synthesis, chlorophyll formation and photosynthesis.…”
Section: Minerals Content Of Samplesmentioning
confidence: 99%
“…Quality parameters such as protein, oil carbohydrate, minerals and anti-nutritional factors are influenced by such factors as temperature, rainfall, sunshine, soil minerals etc [2]. Temperature effects on protein, carbohydrate and lipid formation in legumes are well documented [1,3]. However there appears to be some controversies on nutrients accumulation in grains during low temperature and high rainfall accompanying changes in climatic conditions [4,5].…”
Section: Introductionmentioning
confidence: 99%